Open Randomized Multicenter Study to Evaluate Safety and Efficacy of Low Molecular Weight Sulfated Dextran in Islet Transplantation. Issue 3 (March 2019) - von Zur-Mühlen, Bengt; Lundgren, Torbjörn; Bayman, Levent; Berne, Christian; Bridges, Nancy; Eggerman, Thomas; Foss, Aksel; Goldstein, Julia; Jenssen, Trond; Jorns, Carl; Morrison, Yvonne; Rydén, Mikael; et al.
Abstract : Background: When transplanted human pancreatic islets are exposed to blood during intraportal infusion, an innate immune response is triggered. This instant blood-mediated inflammatory reaction (IBMIR) activates the coagulation and complement cascades and leads to the destruction of 25% of all transplanted islets within minutes, contributing to the need, in most patients, for islets from more than 1 donor. Low molecular dextran sulfate (LMW-DS) has been shown in experimental settings to inhibit IBMIR. Methods: The Clinical Islet Transplantation consortium 01 study was a phase II, multicenter, open label, active control, randomized study. Twenty-four subjects were randomized to peritransplant intraportal and systemic treatment with either LMW-DS or heparin, targeting an activated partial thromboplastin time of 150 ± 10 seconds and 50 ± 5 seconds, respectively. C-peptide response was measured with a mixed meal tolerance test at 75 and 365 days after transplant. Results: Low molecular dextran sulfate was safe and well tolerated with similar observed adverse events (mostly attributed to immunosuppression) as in the heparin arm. There was no difference in the primary endpoint (stimulated C-peptide 75 ± 5 days after the first transplant) between the 2 arms (1.33 ± 1.10 versus 1.56 ± 1.36 ng/mL, P = 0.66). Insulin requirement, metabolic parameters, Clarke and HYPO score, quality of life, and safety were similar between the 2 treatments groups. Conclusions: Even with low dosing, LMW-DS showed similar efficacy in preventing IBMIR to promote islet engraftment when compared to "state-of-the art" treatment with heparin. Furthermore, no substantial differences in the efficacy and safety endpoints were detected, providing important information for future studies with more optimal dosing of LMW-DS for the prevention of IBMIR in islet transplantation. Abstract : Supplemental Digital Content is available in the text.